2002
DOI: 10.1016/s0038-1098(02)00202-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional superconductivity in the infinite-layer compound Sr0.9La0.1CuO2 in entire region below Tc

Abstract: The infinite-layer compound ACuO2 (A = alkaline-earth ions) is regarded as the most suitable material for exploring the fundamental nature of the CuO2 plane because it does not contain a charge-reservoir block, such as a rock-salt or a fluorite like block. We report that superconductivity in the infinite-layer compound Sr0.9La0.1CuO2 is of a three-dimensional nature, in contrast to the quasi two-dimensional superconducting behavior of all other cuprates. The key observation is that the c-axis coherence length … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…More concrete evidence for this can be found from a scaling analysis of the fluctuation-induced magnetization for the high-field region. 20,21 In our previous report, 22 we showed that the high-field magnetization scales excellently with the scaling parameter ͓TϪT c (H)͔/ (TH) 2/3 , implying weak fluctuation effects. perature T irr (H) is defined as the temperature at which the simple criterion M FC /M ZFC ϭ0.98 holds.…”
Section: Resultsmentioning
confidence: 58%
“…More concrete evidence for this can be found from a scaling analysis of the fluctuation-induced magnetization for the high-field region. 20,21 In our previous report, 22 we showed that the high-field magnetization scales excellently with the scaling parameter ͓TϪT c (H)͔/ (TH) 2/3 , implying weak fluctuation effects. perature T irr (H) is defined as the temperature at which the simple criterion M FC /M ZFC ϭ0.98 holds.…”
Section: Resultsmentioning
confidence: 58%
“…It is known that the Simon-Lee scaling law is applicable with T T c and H H c2 (0). Taking T c = 43 K and H c2 (0) = 14 T [29], one may argue that the inapplicability of Simon-Lee scaling law here is due to the relatively high field used. From fig.…”
mentioning
confidence: 93%
“…However, this cannot be the case since the main contribution from the Doppler shift effect is induced by the field component parallel to the c-axis, provided the sample is anisotropic (the anisotropy is about 9, as shown in ref. [29]). Therefore, the d-wave scaling law should be roughly valid for granular samples if it had a d-wave symmetry.…”
mentioning
confidence: 99%
“…On the other hand, they also find significant anisotropy be-tween magnetic fields H ≤ 5 T oriented parallel and perpendicular to the CuO 2 planes, with an anisotropy ratio γ = ξ c /ξ ab = H ab c2 /H c c2 = 9.3, which is larger than γ = 5 observed in YBa 2 Cu 3 O 7−δ although much smaller than γ = 55 observed in optimally doped Bi 2 Sr 2 CaCu 2 O 8−δ . [5,11,12,13] It is interesting to note that the only major crystallographic difference between the a-b and the c directions in Sr 0.9 La 0.1 CuO 2 is the presence of oxygen in the a-b plane, which allows coupling of adjacent Cu spins and has been implicated as the cause of antiferromagntic ordering or spin fluctuations in other members of the high-T c cuprate family, as well as a possible mechanism for superconducting pairing. The importance of the CuO 2 planes to the SC in Sr 0.9 M 0.1 CuO 2 is further supported by the fact that Ni substitution on the Cu site rapidly suppresses T c whereas out-of-plane Gd substitution on the Sr site leaves T c unchanged.…”
mentioning
confidence: 99%